2013
DOI: 10.1200/jco.2012.47.3116
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 12-Gene Colon Cancer Recurrence Score in NSABP C-07 As a Predictor of Recurrence in Patients With Stage II and III Colon Cancer Treated With Fluorouracil and Leucovorin (FU/LV) and FU/LV Plus Oxaliplatin

Abstract: A B S T R A C T PurposeAccurate assessments of recurrence risk and absolute treatment benefit are needed to inform colon cancer adjuvant therapy. The 12-gene Recurrence Score assay has been validated in patients with stage II colon cancer from the Cancer and Leukemia Group B 9581 and Quick and Simple and Reliable (QUASAR) trials. We conducted an independent, prospectively designed clinical validation study of Recurrence Score, with prespecified end points and analysis plan, in archival specimens from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 31 publications
7
110
1
1
Order By: Relevance
“…In clinical practice, the patients treated were more complex because they may take other drugs affecting efficacy of chemotherapy regimens. Moreover, previous trials did not clearly indicate that if the heterogeneous group of stage III colon cancer patients, such as status of molecular profile with same benefit from FOLFOX regimen [10,11].…”
Section: Backgroundsmentioning
confidence: 97%
“…In clinical practice, the patients treated were more complex because they may take other drugs affecting efficacy of chemotherapy regimens. Moreover, previous trials did not clearly indicate that if the heterogeneous group of stage III colon cancer patients, such as status of molecular profile with same benefit from FOLFOX regimen [10,11].…”
Section: Backgroundsmentioning
confidence: 97%
“…Yothers et al reported that the 12-gene Recurrence Score provides additional information beyond the conventional clinical and pathological factors 28 ; this score is a predictor of recurrence risk that was developed using gene expression data 29 . In clinical practice, these factors could improve decision-making regarding adjuvant chemotherapy for patients with Stage and colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the medical journals, a total of 767 parallel group RCTs were reported from January 2013 to December 2014: 179 in the New England Journal of Medicine, 108 in The Lancet, 108 in The Journal of the American Medical Association, 26 in Annuals of Internal Medicine, 122 in The Lancet Oncology, and 224 in the Journal of Clinical Oncology. We found five papers [5,41,22,21,40] covering four types of CBPTI plots (two papers presented STEPP. One was selected for our study).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A Bland-Altman plot is recommended for this example [7]. The lack of uncertainty is a major limitation of [41] basis of the principles of visual display, Figure 3.2 shows two limitations. The readers have to read the legend to check which thickness of line belongs to which treatment group.…”
Section: Distinguishing the Outcome E↵ect For Each Treatment Groupmentioning
confidence: 99%
See 1 more Smart Citation